(Re)Envisioning Human Service Labor: Worker-Owned Cooperative Possibilities. Issue 2 (4th May 2017) - Matthew, Rebecca A.
ABSTRACT: This article explores the viability of worker-owned cooperatives as a promising human service delivery model that prioritizes the well-being of both care recipients and providers. In so doing, the current labor conditions of those providing direct care services are presented, followed by a review of cooperatives as a promising countertrend within human service delivery. Three case examples of worker-owned, direct-care cooperatives are presented, concluding with a discussion of the challenges and possibilities of this model and suggested next steps as we continue to (re)imagine modes of care provision premised on worker sovereignty, economic equality, and social justice.